Is there any influence of breastfeeding on the cerebral blood flow? A review of 256 healthy newborns - Monteiro,Alexandra Maria Vieira (2012)
OBJECTIVE: To investigate whether breastfeeding influence the cerebral blood-flow velocity. MATERIALS AND METHODS: The present study included 256 healthy term neonates, all of them with appropriate weight for gestational age, 50.8% being female. Pulsatility index, resistance index and mean velocity were measured during breastfeeding or resting in the anterior cerebral artery, in the left middle cerebral artery, and in the right middle cerebral artery of the neonates between their first 10 and 48 hours of life. The data were analyzed by means of a paired t-test, Brieger's f-test for analysis of variance and linear regression, with p < 0.01 being accepted as statistically significant. RESULTS: Mean resistance index decreased as the mean velocity increased significantly during breastfeeding. Pulsatility index values decreased as much as the resistance index, but in the right middle cerebral artery it was not statistically significant. CONCLUSION: Breastfeeding influences the cerebral blood flow velocities.